(untitled) (KYAMC Journal, 2017)
Background: Patient’s management during emergency differs significantly between countries. However, technological advancement and requirement of quality support service as well as survivality is a great concern towards reduced hospital mortality. Aim and Objectives: The aim of this study is to find out patient’s characteristics admitted at GICU of Khwaja Yunus Ali Medical College Hospital (KYAMCH) in order to investigate selected variables like; the duration of stay at GICU, their health problems on admission, diagnosis and prognosis including certain demographic characteristics in particular. Methods and Materials: This was an exploratory study on patient’s characteristics during the period from January to June 2015 at GICU of KYAMCH. The data were collected through record review according to variables available on GICU admission register. Results: Total 163 cases were studied in 6 months. Among them 98 (60.12%. were male & 65 (39.88%) were female. The mean age of admitted male patients were 47 & in female it was 40 years with mean ± 16 and 17 years respectively. In addition GICU stays were found up to 5 days among 76.58% patients. The study revealed septic shock, cancer, injury and CVD as the common emergencies that needed skillful attention. Moreover, death and Discharge on Risk Bond (DORB) were found unwanted outcomes (52.23%) that also need to be addressed through developing skilled management protocol at GICU of concern tertiary care hospital. Conclusions: The findings will help hospital managers to identify necessary support needed as well. It will also help to identify emergency management skills needed for the GICU personnel team members in particular. Thus it can be a basis for the hospital administrators to take appropriate measures in towards reducing hospital mortality rate as well. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 678-680